(untitled) (Research, Society and Development, 2024)
Objective: This study aims to analyze the effects of therapeutic use of melatonin in adults, observing possible applications to ensure improvement in sleep quality. Methodology: It is a narrative review based on specialized literature, through consultation of books and scientific articles selected from the collection of the Central Library of the Federal University of Alfenas-MG, Alfenas campus, and databases such as Pubmed, Scielo, and Uptodate. Results and Discussion: The studies found on the use of exogenous melatonin support the hypothesis that there was an impact on sleep disorders in adults, resulting in an improvement in the sleep of the analyzed population in the raised articles, which addressed the effects and recommendations of melatonin for the treatment of various comorbidities. Conclusion: After the analysis and study of the presented articles, it is concluded that the therapeutic use of melatonin is plausible. It is effective in adults at low dosages during the night and for a short period, as there are few studies evaluating its effectiveness and side effects in long-term use. However, gaps in research on melatonin and its relationship with sleep quality were demonstrated when considering broader aspects such as age, gender, ethnicity, comorbidities, duration of use, among other factors.